Application of Restorative Justice to Corruption : Penerapan Restorative Justice Terhadap Tindak Pidana Korupsi - Laia , Alisokhi (UPMI Proceeding Series, 2023)
This study aims to analyze law enforcement of criminal acts of corruption in village funds that are not resolved through a restorative justice approach and to analyze restorative justice formulations in criminal acts of corruption in the management of village funds. Based on the results of this study that (a) Law enforcement of criminal acts of corruption in village funds has not been resolved through a restorative justice approach, this is because corruption is an extraordinary crime and is a formal offense in nature where restitution of state losses does not eliminate the crime, but in the level of practice of the restorative justice approach has been carried out in cases of corruption whose value is considered to be less than the cost of handling the case. The principles of fast, simple and low cost and the importance of considering the Attorney General's Office Decree Number B-765/F/Fd.1/04/2018 concerning technical guidelines for handling corruption cases at the investigative stage as well as directions from the Head of the Attorney General's Office of the Republic of Indonesia can be a normative reason for enforcement restorative justice in cases of criminal acts of corruption in village funds (b) the application of restorative justice in criminal acts of corruption in the management of village funds is carried out to provide guarantees of legal certainty for law enforcers in resolving cases of corruption in the management of village funds. As for the application of restorative justice, namely that the perpetrator is the first time committing a crime, the value of state financial losses due to corruption cases in the management of village funds is not more than Rp. 150,000,000.00 (one hundred and fifty million rupiah) and the perpetrator is not a recidivist of a crime.